(untitled) (Research, Society and Development, 2022)
In view of the new coronavirus – COVID-19 pandemic scenario, the Youth and Adult Education modality (YAE), mostly composed of students with an educational exclusion history, has become even more vulnerable due to the suspension of the school activities, creating a greater challenge to the education systems. In addition to education, several sectors of society were affected and because of the necessity of social distancing, the schools had to adhere to the proposal of remote teaching in order to carry out the school schedule. This paper approaches the remote teaching theme to reflect and discuss the impact of the COVID-19 pandemic on the YAE system, through the analysis of students’ experiences that are currently enrolled in that teaching modality associated with a municipal public system school in Senador Pompeu – Ceará. Specifically, we analyzed the students’ performance and learning skills during this pandemic context, in which the classes were performed in the remote learning system. This research is based on a qualitative approach and it has as methodological principle the bibliographical and explanatory research, subsidized by some authors, such as: Haddad and Di Pierro (2000), Moura (2003), Scortegagna and Oliveira (2006), Martins Correia (2021), which theoretical basis are essential to the foundation of this study.